1990
DOI: 10.1080/00288233.1990.10428416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clover cultivar on production and nitrogen fixation in clover-ryegrass swards under dairy cow grazing

Abstract: 'Grasslands Huia', 'GrasslandsPitau', 'GrasslandsKopu', Aranandresidentwhiteclovers and 'GmsslandsPawem' red cloverweresownwith perennial ryegrass and examined for production (over 3 years) and nitrogen (N) fixation (over 2 years) under dairy cow grazing. Total sward production was similarfor all treatments, although grass-only plotswere 11and20%loweryieldingin Years 1 and 2 respectively. Pawem produced the mostcloverin Year I, but the leastin Years2 and3. In Years 1 and 2, the best-producing white clover cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 16 publications
1
25
0
1
Order By: Relevance
“…The annual average amount of N fixed in the mowing trial on the Matapiro soil was similar to that reported on some steepland pastures in the Waikato (Ledgard et al 1987). The annual average amount of N fixed in the trial on the Mangatea soil was similar to (Ledgard et al 1990;Ledgard 1991) that (Edmeades et al 1986;Ledgard et al 1990) reported on some high fertility dairy farms. In all comparisons, it is noted that the 15 N dilution technique as used in this paper gives a minimum rate of N fixation as the transfer of symbiotically derived N from clovers to grass was not measured (Edmeades & Goh 1978).…”
Section: Discussionsupporting
confidence: 65%
“…The annual average amount of N fixed in the mowing trial on the Matapiro soil was similar to that reported on some steepland pastures in the Waikato (Ledgard et al 1987). The annual average amount of N fixed in the trial on the Mangatea soil was similar to (Ledgard et al 1990;Ledgard 1991) that (Edmeades et al 1986;Ledgard et al 1990) reported on some high fertility dairy farms. In all comparisons, it is noted that the 15 N dilution technique as used in this paper gives a minimum rate of N fixation as the transfer of symbiotically derived N from clovers to grass was not measured (Edmeades & Goh 1978).…”
Section: Discussionsupporting
confidence: 65%
“…Aran and Kopu were markedly higher-yielding than all other cultivars. A similar experiment under dairy cow grazing in Waikato also showed high productivity from Aran and Kopu during the first 2 years, and greater production by Aran in Year 3 (Ledgard et al 1990). Other experiments have also shown highest clover production from large-leaved cultivars under mowing or rotational grazing systems (Widdup & Turner 1983;van den Bosch et al 1986;Frame & Boyd 1987), whereas under continuous grazing, small-leaved highly stoloniferous cultivars are often more productive (Brock 1988;Evans et al 1992).…”
Section: Production By Clover Cultivars and Interaction With Nitrogenmentioning
confidence: 95%
“…Several New Zealand studies have shown greater production by large-leaved cultivars of white clover grown in mixed swards with no N fertiliser application (Widdup & Turner 1983;van den Bosch et al 1986;Ledgard et al 1990). Only one recent experiment in New Zealand has compared cultivars under different N regimes.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study of differences in N 2 fixation between white clover cultivars in New Zealand (Ledgard et al 1990), it was concluded that there were no inherent differences in the capacity of different cultivars to fix N, and thus that N 2 fixation was not a basis for substituting one for another. Generally speaking, in breeding for maximum dry matter or total N accumulation, clover breeding programs might indirectly select for maximal N 2 fixation.…”
Section: Differences In N 2 Fixation Capacity Between Species and Culmentioning
confidence: 99%